Pedagogia do teatro e alteridade: desafios, possibilidades e reflexões na realidade escolar - Almeida, Aline Catiane Paz (2018)
The present work has as the object of investigation the pedagogy of the theater in the perspective of enabling the conquest of alterity in the school context of a group of the third year of elementary education in a public school located in the capital of Paraíba. The purpose of this work is to develop the pedagogy of theater in the school that contemplates the development of children, raising their selfesteem, working the alterity, in sense of valuing and respecting each student in its unique and individual being, even being inserted in a collective action. Thus, it intends here to point out ways that lead to the thought and construction of identities that are empowered, and through the alterity, it puts themselves in the place of the other, increasing their critical sense, generating a relation of interaction and respect with the other with a view of making the teaching and learning process enjoyable and expressive to the student. The theoretical conduction was based on studies on theater and alterity in the school context. Methodologically, the research developed is qualitative approach, from the participant research perspective. As techniques and methods for the development of the work, the data were generated by a group of 27 elementary students in interactive circles, as well as the development of theatrical games and dramatic games, study visits, reading of various literary texts, storytelling and, finally, there were consolidated by performing a play as the result of the semester work with the students. As a conclusion, we can infer that, despite all the difficulties faced on the course of the research, the school is one of the most recurrent and active mediations that cross and compose the relationship of the children with the theatrical language. Therefore, the analyzes carried out in here demonstrate that the multiple mediations permeate and constitute the students' experiences and their perception of alterity in the processes of creation, contributing to the formation of their identities as subjects that create the theater in the school.